Application of PjBL Model With Capcut Media to Improve Speaking Skills In XII High School Grades - nurhidayah, elly; Indrayanti, Tri (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2025)
This study aims to describe the application of speaking skills of XII grade students at Al Islam Krian High School through the application of the Project Based Learning (PjBL) learning model with CapCut media, especially in Indonesian language subjects. This research is a Classroom Action Research (PTK) which is carried out in two cycles, namely cycle I and cycle II. The results obtained in cycle I, only 21.22% of students were complete in speaking skills, with an average score of 65.09. This was caused by students' lack of interest in the model and media used. After evaluation, in cycle II, the application of PjBL and the use of CapCut showed significant improvement. All students (100%) were successfully completed with the average score rising to 88.78. This research shows that the application of the PjBL model and CapCut media is effective in improving students' speaking skills, as well as making the learning process more interesting and creative. The results of this study are expected to be a reference for educators in applying more innovative learning methods, so that students can actively contribute to learning and improve their language skills optimally. Keyword: Bahasa Indonesia, Speaking, PjBL, CapCut